Vote Swapping in Representative Democracy - Dindar, Hayrullah; Laffond, Gilbert; Laine, Jean (Springer-Verlag Berlin, 2015)
We investigate group manipulation by vote exchange in two-tiers elections, where voters are first distributed into districts, each with one delegate. Delegates' preferences result from aggregating voters' preferences district-wise by means of some aggregation rule. Final outcomes are sets of alternatives obtained by applying a social choice function to delegate profiles. An aggregation rule together with a social choice function define a constitution. Voters' preferences over alternatives are extended to partial orders over sets by means of either the Kelly or the Fishburn extension rule. A constitution is Kelly (resp. Fishburn) swapping-proof if no group of voters can get by exchanging their preferences a jointly preferred outcome according to the Kelly (resp. Fishburn) extension. We establish sufficient conditions for swapping-proofness. We characterize Kelly and Fishburn swapping-proofness for Condorcet constitutions, where both the aggregation rule and the social choice function are based on simple majority voting. JEL Class D71, C70.
15th International Conference on Group decision and negotiation (GDN) -- JUN 22-26, 2015 -- Warsaw, POLAND
Keywords: Representative Democracy; Vote Swapping; Vote Exchange; Group Manipulation; Manipulation